Study of Material Flow Analysis Mapping in Supply Management Chain for the Management of Non Functional Device Transformers - Annisa Maudi Syafitri; Farida Pulansari (Newinera Publisher, 2025)
This research investigates the optimization of supply chain management for Non-Functional Device (NFD) transformers at PT XYZ through the integration of Material Flow Analysis (MFA) and Analytic Hierarchy Process (AHP). The study addresses the issue of material accumulation and environmental impact arising from inefficient management of decommissioned transformers. MFA to model and evaluate three management scenarios based on mass flow and carbon emissions, while AHP facilitated decision-making by prioritizing five key criteria and eleven sub-criteria. Data were collected through interviews, questionnaires, and internal company records. The results show that Scenario 3 eaturing transformer oil regeneration and component reuse yielded the lowest carbon emissions (101.981 kg CO₂/month) and the highest priority score (0.628) in AHP analysis, with regulatory compliance emerging as the most critical factor. This indicates that Scenario 3 offers the most sustainable and efficient strategy, enabling the company to reduce emissions, recover material value, and improve overall supply chain performance